Integrating Education, Technology, and Local Institutions for Community-Based Waste Management: A Sustainable Development Approach in Bulusan Village, Banyuwangi - UMAR, YASA PALAGUNA; Susilo, Bambang; Setiawan, Adi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2026)
This study presents an integrated community-based waste management program in Bulusan Village, Banyuwangi, aligned with Sustainable Development Goals 11, 12, and 13. Using participatory action methods, the program combined environmental education, an organic waste shredder, biopores, compost bags, and a community waste bank. Results showed a 74.2% average increase in waste literacy, a 30% reduction in household waste, and enhanced community engagement and governance. The findings demonstrate that integrating education, technology, and local institutions effectively transforms household waste management and provides a replicable model for sustainable, circular communities in post-landfill settings.